2016
DOI: 10.11646/zootaxa.4066.3.9
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>A new species of <em>Microhyla</em> (Anura: Microhylidae) from Sri Lanka: </strong><strong>an integrative taxonomic approach</strong></p>

Abstract: Species boundaries of Microhyla rubra of India and Sri Lanka were assessed using the following criteria: genetic barcoding, morphology, and vocalization. We use a ca. 500 bp fragment of the 16S rRNA mitochondrial gene and show that there is an uncorrected pairwise distance of 2.7-3.2% between the Indian and Sri Lankan populations of M. rubra. We show that they are different in several call characteristics such as, dominant frequency, call duration, call rise time and pulse rate. Morphologically, the Sri Lankan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 0 publications
5
24
0
Order By: Relevance
“…Previously, M. ornata was considered as a widely distributed species in South Asia, even though only a few selected populations from Karnataka (e.g., Matsui et al 2005 Kerala (Howlader et al 2015) had been genetically identified. Based on extensive sampling, we show that M. ornata has a narrow distribution restricted to Peninsular India (and Sri Lanka, as previously indicated by Wijayathilaka et al 2016). More specifically in India, the presence of M. ornata is currently only confirmed in the states of Tamil Nadu, Kerala, Karnataka, Maharashtra, and Andhra Pradesh (Figures 1(A) and S2).…”
Section: Dna Barcoding Reveals Four In One Speciessupporting
confidence: 75%
“…Previously, M. ornata was considered as a widely distributed species in South Asia, even though only a few selected populations from Karnataka (e.g., Matsui et al 2005 Kerala (Howlader et al 2015) had been genetically identified. Based on extensive sampling, we show that M. ornata has a narrow distribution restricted to Peninsular India (and Sri Lanka, as previously indicated by Wijayathilaka et al 2016). More specifically in India, the presence of M. ornata is currently only confirmed in the states of Tamil Nadu, Kerala, Karnataka, Maharashtra, and Andhra Pradesh (Figures 1(A) and S2).…”
Section: Dna Barcoding Reveals Four In One Speciessupporting
confidence: 75%
“…This is also true for the genus Microhyla , widespread throughout the tropics across India, Sri Lanka, Indonesia, archipelagos of Ryukyu of Japan and Sulu of Philippines [ 21 ]. So far, 39 species of the genus have been identified [ 10 , 21 ], of which four (ca. 10%) are found in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…From Microhyla maculifera, the new species differs by having a larger body size (SVL, males: 16.9-17.4 mm vs. 12-13.3 mm in M. maculifera), slender body (vs. moderately stout), presence of finger disc (vs. absent), presence of two metatarsal tubercles (vs. single metatarsal tubercle) (Inger 1989;Bain & Nguyen 2004). The new species differs from Microhyla mihintalei by having a smaller body size (SVL, males: 16.9-17.4 mm vs. 21.7-27.3 mm in M. mihintalei), grayish-black vocal sac (vs. dark blackish-brown), presence of finger and toe disc (vs. absent), absence of lateral skin band (vs. light gray band extending from behind the eye to the groin) (Wijayathilaka et al 2016). From Microhyla minuta, the new species differs by having larger body size (SVL, males: 16.9-17.4 mm vs. 14.7 -15.9 mm in M. minuta), first finger (F1) length more than the half-length of second finger (F2) i.e.…”
Section: Resultsmentioning
confidence: 82%
“…Studies on the genus Microhyla in the Indian subcontinent have been very narrow and limited. However, there are a handful of studies on this family that have been published in recent years (Seshadri et al 2016a;Howlader et al 2015;Poyarkov Jr et al 2014;Dutta and Ray 2000;Hasan et al 2014;Wijayathilaka et al 2016). As noted in previous publications (Seshadri et al 2016a;Howlader et al 2015), there might be several new species and new distributional records in Indian subcontinent.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation